(untitled) - Lourmière, Guillaume (Can Tho, 2020)
Vietnam is one of the largest shrimp producers in the world, it was ranked 3rd in the world in 2018. More than 80% of the Vietnamese shrimp are produce in Mekong Delta’s farms. In quantity, it’s the 2nd aquaculture production in Vietnam, and the 1st Vietnamese aquaculture production for its economic value, the main cultured species is the whiteleg shrimp (Litopenaus vannamei). However, with the recent intensification of shrimp farming in Mekong Delta, more and more shrimp diseases occurred in farms. Last few years, many new diseases affected shrimps in Mekong Delta, which often resulted in mass shrimp mortality and a big economic loss for farmers. To understand why and how these diseases occur, during the 2nd semester of 2019, a basic surveillance was carried out in the major whiteleg shrimp culture areas of Mekong Delta: in Soc Trang, Bac Lieu and Ca Mau provinces, with a motive of mapping disease type, parasites and clinical signs using a GIS. 28 ponds were sampled in 6 different districts, samples were collected directly on farms, with farmers agreement, and brought to Can Tho University, College of Aquaculture and Fisheries laboratories for analysis, only shrimps showing pathological clinical signs were sampled. Analysis were carried out using histopathological, bacterial isolation and PCR techniques. All the data collected from the analysis were compiled into a MS-Excel spreadsheet, and then imported to ARC GIS software by ESRI to create maps showing the result of the analysis. During the study, EMS caused by Vibrio parahaemolyticus bacteria was the main disease found, and gregarine parasites which are suspected to cause WFS were detected in all the sampled ponds. On the other hand, WSD, was almost absent from the studied ponds. EHP and vermiform ATM were also found in low quantity. The maps showing the different infections, parasites and disease, and clinical signs were created to understand better where disease appear and what trigger them. This study is a first shrimp disease mapping attempt in Mekong Delta, it also suggests the continuation of this type of study to evaluate epidemiology, disease transmission and the global knowledges about whiteleg shrimp.
Keywords: Nuôi tôm,Shrimp culture